One new species and one new combination of the genus Neocyrtopsis Liu & Zhang, 2007 (Orthoptera: Meconematinae) from Emeishan, China - Wang, Hai-Jian; Cao, Cheng-Quan; Shi, Fu-Ming (Zootaxa, 2013)
The paper describes one new species, i.e. Neocyrtopsis (Neocyrtopsis) emeishanensis Shi sp. nov., transfers Phlugiolopsis platycata Shi & Zheng, 1994 to the genus Neocyrtopsis and redescribes the species.